Kolāhala - Paramāra, Mohana (Rannāde Prakāśana, 2005)
Samaya – Vasavaso – Gamāra – Khacakāṭa – Toḍa – Saṅketa – Dīvāla – Vimāsaṇa – Pharī ko'ka vāra – Ukaḷāṭa – Samajaṇa – Kolāhala
Short stories. - Gujarati in Gujarati-Schr
Keywords: Short stories; Gujarati